2021
DOI: 10.48550/arxiv.2103.15840
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three-Point Functions in ABJM and Bethe Ansatz

Peihe Yang,
Yunfeng Jiang,
Shota Komatsu
et al.

Abstract: We develop an integrability-based framework to compute structure constants of two subdeterminant operators and a single-trace non-BPS operator in ABJM theory in the planar limit. In this first paper, we study them at weak coupling using a relation to an integrable spin chain. We first develop a nested Bethe ansatz for an alternating SU(4) spin chain that describes single-trace operators made out of scalar fields. We then apply it to the computation of the structure constants and show that they are given by ove… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 81 publications
(116 reference statements)
0
13
0
Order By: Relevance
“…which agrees with the convention in [9] if c = i. To get the corresponding K-matrix we have to solve the equation (5.28)…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…which agrees with the convention in [9] if c = i. To get the corresponding K-matrix we have to solve the equation (5.28)…”
mentioning
confidence: 75%
“…It was shown that these three-point functions can be calculated as an overlap between the finite volume multi-particle state and an integrable initial state. First these quantities were investigated in the AdS 5 /CF T 4 duality [7,8] and recently the method was generalized to the AdS 4 /CF T 3 duality [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the top-down construction of AdS/CFT based on string theory, operators with different conformal dimensions admit different holographic descriptions. For instance in the matrixlike large N limit, operators with O(1) conformal dimension 1 are dual to perturbative string states while operators with O(N ) and O(N 2 ) conformal dimensions correspond to D-branes and backreacted geometries including black holes. The best studied among them are operators dual to string states since they can be analyzed by various approaches such as supergravity, integrability, conformal bootstrap and perturbation theory.…”
Section: Introductionmentioning
confidence: 99%